1989
DOI: 10.1063/1.857508
|View full text |Cite
|
Sign up to set email alerts
|

Goertler vortices in supersonic and hypersonic boundary layers

Abstract: The problem of Goertler vortices in compressible boundary layers over concave walls is considered. At O(1) wavelengths, the instability is governed by parabolic partial differential equations that are solved numerically to determine the effect of various initial conditions on the development of Goertler vortex instability in compressible boundary layers. The results show that both the velocity and temperature fluctuations may lead to a Goertler vortex. The vortex growth rates determined from the present method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 9 publications
6
30
0
Order By: Relevance
“…Numerical effects were used to initiate a disturbance by [5,24], while [46] introduced a forced disturbance. Other numerical studies use boundary layer assumptions with constant curvature walls [14,21,40]. Domrö se et al [5] obtained good qualitative agreement with experiments in a shock impingement-boundary layer interaction by setting the domain width to four times the vortex diameter obtained in experiments.…”
Section: Introductionmentioning
confidence: 87%
“…Numerical effects were used to initiate a disturbance by [5,24], while [46] introduced a forced disturbance. Other numerical studies use boundary layer assumptions with constant curvature walls [14,21,40]. Domrö se et al [5] obtained good qualitative agreement with experiments in a shock impingement-boundary layer interaction by setting the domain width to four times the vortex diameter obtained in experiments.…”
Section: Introductionmentioning
confidence: 87%
“…Ginoux (1971) observed the presence of Goertler vortices in the reattaching flow downstream of a descendent step at a Mach number of 5.3. More recently E1 Hady and Verma (1983), Spall and Malik (1989), Jallade (1990), Aymer de la Chevalerie et al (1991) published numerical results about the compressible Goertler problem, including the pressure gradient as well as wall temperature influence. All these papers are concerned with the instability of supersonic and/or hypersonic flows over concave walls, having a constant streamwise curvature radius.…”
Section: Introduction and Theoretical Remarksmentioning
confidence: 99%
“…Obviously, for moderate free-stream Mach numbers, the structure of the vortices should not be significantly different from their structure in a liquid. Thus, Spall and Malik [13] and Wadey [14] studied long-wave vortices in a gas for which it is necessary to take into account the "growth" of the boundary layer. It has been found that unstable vortices shift toward the outer edge of the boundary layer as the Mach number increases [14].…”
mentioning
confidence: 99%